After Effect of Electroacupuncture at Jiaji Acupoint on the Protein Expression of P2X4, P2X7 in Chronic Constriction Injury Rats - Hui'e CHEN; Mingyu HUANG; Wenying YU; Dong LIN; Lili LIN (康复学报)
Objective:To observe the after effect of electroacupuncture (EA) at Jiaji acupoint on the protein expression of P2X4, P2X7 receptors in chronic constriction injury (CCI) rats so as to explore the regularity of electroanalgesia in neuropathic pain.Methods:Twenty-four adult male Sprague Dawley (SD) rats were screened for thermal pain latency and randomly divided into blank group, model group, 1 hour after EA treatment group and 12 hours after EA treatment group, 6 rats in each group. The CCI models were established in the model group, 1 hour after EA treatment group and 12 hours after EA treatment group. The rats in the 1 hour after EA treatment group and 12 hours after EA treatment group were treated with EA at Jiaji acupoint on both sides for 20 minutes on the 7th day after modeling. Each group was redetermined with thermal pain latency after 7 days of modeling and before drawing materials. Spinal cord bulging and the protein expression of P2X4, P2X7 were detected by Western Blot.Results:Compared with the blank group, the thermal pain latency of the model group decreased significantly (P<0.05) after 7 days of surgery. After intervention, the thermal pain latency of the 1 hour after EA treatment group was significantly higher than that of the model group (P<0.05), but that of the 12 hours after EA treatment group was not significantly higher (P>0.05). The protein expression of P2X4, P2X7 level in the model group increased significantly (P<0.05) compared with that in the blank group. The protein expression of P2X4, P2X7 level in the 1 hour after EA treatment group decreased significantly (P<0.05) compared with that in the model group, but that in the 12 hours after EA treatment group did not decrease significantly (P>0.05).Conclusion:Electroanalgesia might decrease the thermal pain latency through the protein expression of P2X4, P2X7 receptors in CCI rats. The after effect can be extended for one hour or more than one hour, with a certain regularity of aging.